The Importance of Liquidity and Profitability in Enhancing the Banking Value in Private Banks for the Period 2016 - 2019 - Wadi, Mohamed Hassan; Dhaireb, Mohamed Samir (Journal of Economics and Administrative Sciences, 2021)
The article aims to study the liquidity that is required to be provided optimally and the profitability that is required to be achieved by the bank, and the impact of both of them on the value of the bank, and their effect of both liquidity and profitability on the value of the bank. Hence, the research problem emerged, which indicates the extent of the effect of liquidity and profitability on the value of the bank. The importance of the research stems from the main role that commercial banks play in the economy of a country. This requires the need to identify liquidity in a broad way and its most important components, and how to measure it. For the purpose of avoiding liquidity risks, liquidity should be managed by urging the bank to adopt good liquidity management and to achieve the profits that the bank wants to achieve by employing the liquidity available to it. It represents an important factor for increasing profits and increasing the confidence of shareholders and depositors; thus, maximizing the wealth of shareholders and the bank’s wealth and, hence, raising the bank value. Consequently, this article is based on a main hypothesis that "there is no effect of profitable and liquidity on the bank value". This in turn is divided into two sub-hypotheses as follows: H1. There is no effect of quick liquidity on the bank value. H2. There is no effect of the return on deposits on the bank value In order to achieve the objectives and hypotheses of the study, the mathematical indicators were studied and analyzed to find the relationship between the variables and the effect according to statistical methods, where the research used the a simple regression statistical method, Is used by using the Statistical Package for Social Sciences (SPSS), and the quantitative measures, which included such indicators as the quick liquidity indicators to measure liquidity, the return on deposits to measure profitability, and Tobin’s Q bank value measurement. The research sample consisted of four private banks (Middle East Bank, Gulf Bank, Al-Ahli Bank and Bank of Baghdad) for the period from 2016 to 2019. The most important conclusions reached by the research were the lack of effect of both the liquidity and profitability on the value of the bank. The research gave a number of recommendations, the most important of which is to urge banks to reduce the excess liquidity ratios and exploit them in different investment fields, as well as to go towards resources that achieve higher profitability rates than others that are characterized by their low cost. The research also recommended not to keep excess liquidity ratios at a high rate because of their effect on the profitability that the bank seeks to achieve